Advancement in IoT-enabled Healthcare System: a Systematic Review of Technologies and Securities Issues - Amelia Putri; Rian Ardianto (Penelitian dan Pengembangan Ilmu, 2024)
IoT (Internet of Things)-based health systems offer the potential for digital transformation in healthcare, but face significant security challenges that require serious attention. This research aims to identify and analyze security challenges in IoT-based health systems and evaluate existing solutions to overcome these challenges. The research method used is a systematic review using the PRISMA approach, collecting articles from reputable databases such as Scopus, IEEE Xplore, and PubMed. The research results show that although IoT technology can improve real-time patient monitoring and operational efficiency, vulnerability to cyberattacks and data privacy concerns remain major obstacles. The implications of these findings indicate the need for the development of stronger security solutions and comprehensive protection strategies to ensure successful implementation of IoT in health systems.